Studi Literatur Keberadaan dan Sebaran Burung Rangkong (Bucerotidae) di Aceh - Mulia Nazila; Rizka Raihani; Rizqa Savira; Muzayyin Khairi; Citra Dara Mutia; Aida Fithri; Widya Sari (Jurnal Bioleuser, 2025)
Hornbills (Family Bucerotidae) are animals that play an important role in maintaining the balance of forest ecosystems, but their existence is increasingly threatened due to various factors such as habitat destruction and hunting. This study aims to determine the distribution of hornbill species, and their habitat in Aceh Province. The method used was a literature study with the keywords “hornbills,” “diversity,” and “Aceh,” using the Google Scholar and ResearchGate databases. The results showed that plank hornbills (Buceros bicornis) were found in Aceh Besar, Aceh Selatan, Aceh Jaya, Aceh Barat, Aceh Tamiang, Gayo Lues, and Nagan Raya. Rhinoceros hornbills (Buceros rhinoceros) are found in Aceh Besar, Aceh Selatan, Aceh Jaya, Aceh Singkil, Aceh Tamiang, Aceh Tenggara, Bener Meriah, Gayo Lues, Nagan Raya, and Bireuen. The white-bellied hornbill (Anthracoceros albirostris) is found in Aceh Besar and Aceh Tamiang, while the black-bellied hornbill (Anthracoceros malayanus) is only found in Aceh Tamiang. The ivory hornbill (Rhinoplax vigil) is distributed in Aceh Tamiang, Langsa, Pidie Jaya, and Gayo Lues, while the crested hornbill (Anorrhinus galeritus) and wreathed hornbill (Rhyticeros undulatus) are found in Southeast Aceh. This study provides an overview of the distribution of hornbill species in Aceh that can serve as a basis for conservation efforts and sustainable habitat management.